Enhancing Vocabulary Mastery Through Digital Image Media and Project-Based Learning: A Classroom Action Research with Third-Grade Students with Speech Disorders - Anggraini, Gustina; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
This classroom action research investigated the effectiveness of digital image media based on Project-Based Learning (PBL) in enhancing vocabulary abilities among third-grade students with speech disorders. Four students aged 8-9 years at YPPSB 3 Elementary School, Sangatta Utara, participated in this study conducted across three cycles following the Kemmis and McTaggart model. Data were collected through structured observations, vocabulary tests (pretest and posttest), and documentation of learning activities. Results demonstrated significant progressive improvements in students' vocabulary abilities. Mean scores increased from 48.94% at pre-action to 54.53% in Cycle I, 71.41% in Cycle II, and 82.31% in Cycle III, representing a total improvement of 33.37%. By Cycle III, 75% of students achieved the "Developing Very Well" category, while 25% reached "Developing as Expected," with no students remaining in lower developmental categories. The intervention enhanced both receptive abilities (listening and comprehension) and productive abilities (speaking and retelling). Digital image media provided concrete visual stimuli supporting word-meaning associations, while the PBL approach fostered active engagement, collaboration, and contextual learning. The combination proved effective in creating enjoyable, meaningful, and inclusive learning experiences for children with speech disorders, confirming that multimodal technology-enhanced instruction addresses complex communication needs and narrows vocabulary gaps typically widening over time in this population.